Approval on the suitability of the use of marine space for the placement of planting Bagan by traditional fisherman in the coastal of Kapedi Village - Rina Yulianti; Safi (Technium Social Sciences Journal, 2023)
Apart from working as fishermen, the coastal community in Kapedi Village also catch fish by planting bagan in coastal waters. Bagan is very effective as a fishing tool. The fish caught using this bagan are of good quality and are not physically damage so that they can compete in traditional markets. Besides that, catching fish using a bagan is not too risky for the safety of the fishermen. Almost all of the fishermen from Kapedi Village stopped fishing by boat and switched to planting bagan on the surface of the coastal waters. The purpose of this study was to determine the practice of controlling coastal waters by traditional fishermen who plant bagan fishing gear and to assess the suitability of these traditional fishing activities based on existing regulations. To achieve the objectives of this study, empirical juridical research methods have been used with a fact approach. The results of the study show that the traditional fisherman planting bagan in Kapedi Village is one of the subjects who can take advantage of sea space, therefore they are required to have Sea Space Utilization Activity Conformity (Kesesuaian Pemanfaatan Ruang Laut) issued by the Ministry of Maritime Affairs and Fisheries. All bagan planting activities on the surface of coastal waters are required to have a Sea Space Utilization Activity Conformity (KPRL) Form of Sea Space Utilization Activity Suitability for fishermen in Kapedi Village based on Government Regulation Number 21 year 2021 in the form of facilitation by the Regional Government.